Y chromosomes and Irish phylogeography - Moore, Laoise Teresa (Trinity College (Dublin, Ireland). Department of Genetics, 2005)
A High-Resolution Y Chromosome Survey of Ireland. In order to investigate the origins of the Irish population and to describe the population genetic events that have shaped the extant Irish gene pool, Y chromosome genetic variation was analysed in 796 unrelated Irish males. High-resolution Y chromosome haplotypes were constructed by typing for 11 slowly-evolving SNP markers and 17 quicky-evolving microsatellite markers. Regional Irish genetic variation was examined and Irish Y chromosome genetic variation was placed in a European context by comparison with data from other European populations. The study revealed a high frequency of the putatively western European Palaeolithic Hg R1b3 in Ireland. When the Irish population is split into regional sub-populations adine in Irish R1b3 frequency is revealed, which rises from the southeast to the northwest. This places northwestern Ireland on the extreme of a European-wide cline in the frequency of this Palaeolithic marker.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin